Clinical Outcome of Glioblastoma Treated in North Wales Cancer Treatment Centre Between 2014 and 2018. (1st October 2022) - Ghosal, Niladri; Burford, Pauline; Showkat, Mehrine; Abbasi, Ehsaan Ullah; Sirelkhatim, Mazin; Kodavatiganti, Ravi; Hind, Ann; Soe, Win
Abstract: AIMS: Glioblastoma (GBM) is the most common primary brain tumour in adults and has a very poor clinical outcome. An audit of the clinical outcomes of patients with glioblastoma at our centre was conducted and compare with the results reported nationally in the National Cancer Registration Service and Hospital Episode Statistics 2007– 2011.[1] ) as well as international standards. METHOD: Patients with GBM in North Wales Cancer Treatment Centre from October 2014 to September 2018 were identified using Canisc databases. We censored 2 patients because of no further follow up due to transferred to other centres. Treatment and outcome data was retrospectively collected using electronic record systems and the case notes. RESULTS: The total 117 patients with GBM were identified. The craniotomy and Debulking surgery was done in 67, Biopsy only in 29 and no surgery in 21 patients. Median OS of all patients was 9.2 months. The median OS in the patient group of under 70 years treated with Concurrent chemo-radiotherapy (60 Gy) followed by adjuvant chemotherapy was 16.9 months. Median OS of patients aged 70 years and above who had "radiotherapy" or "no radiotherapy" were 6.5 months versus 1.9 months respectively. CONCLUSION: Our results are comparable to the national outcomes. We would be reporting further on the differential survivals of different age groups and with results of genetic biomarker stratifications.